Prediction of adverse cardiac events in pregnant women with valvular rheumatic heart disease. Issue 18 (29th June 2020) - Baghel, Jyoti; Keepanasseril, Anish; Pillai, Ajith Ananthakrishna; Mondal, Nivedita; Jeganathan, Yavanasuriya; Kundra, Pankaj
Abstract : Objective: To assess the incidence of adverse cardiac events in pregnant women with rheumatic valvular heart disease (RHD) and to derive a clinical risk scoring for predicting it. Methods: This is an observational study involving pregnant women with RHD, attending a tertiary centre in south India. Data regarding obstetric history, medical history, maternal complications and perinatal outcome till discharge were collected. Eight-hundred and twenty pregnancies among 681 women were included in the analysis. Primary outcome was composite adverse cardiac event defined as occurrence of one or more of complications such as death, cardiac arrest, heart failure, cerebrovascular accident from thromboembolism and new-onset arrhythmias. Results: Of the 681 women with RHD, 180 (26.3%) were diagnosed during pregnancy. Composite adverse cardiac outcome during pregnancy/post partum occurred in 122 (14.9%) pregnancies, with 12 of them succumbed to the disease. In multivariate analysis, prior adverse cardiac events (OR=8.35, 95% CI 3.54 to 19.71), cardiac medications at booking (OR=0.53, 95% CI 0.32 to 0.86), mitral stenosis (mild OR=2.48, 95% CI 1.08 to 5.69; moderate OR=2.23, 95% CI 1.19 to 4.18; severe OR=7.72, 95% 4.05 to 12.89), valve replacement (OR=2.53, 95% CI 1.28 to 5.02) and pulmonary hypertension (OR=6.90, 3.81 to 12.46) were predictive of composite adverse cardiac events with a good discrimination (area under the curve=0.803) and acceptable calibration. A predictive score combining these factors is proposed for clinical utility. Conclusion: Heart failure remains the most common adverse cardiac event during pregnancy or puerperium. Combining the lesion-specific characteristics and clinical information into a predictive score, which is simple and effective, could be used in routine clinical practice.